IMPLEMENTASI ASPEK AFEKTIF DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS IV DI SD NEGERI 36/VI RANTAU PANJANG - Jum'atul Sholehh, Alya; Sunarto; Viktoria, Jetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of affective aspects in mathematics learning among fourth-grade students at SD Negeri 36/VI Rantau Panjang. The background of this research is the significant role of the affective domain including attitudes, interest, motivation, and student responsibility in supporting meaningful and sustainable mathematics learning, as affective components are fundamental alongside cognitive and psychomotor domains in learning objectives. The research employed a descriptive qualitative method with a case study approach. Participants were fourth-grade students at SD Negeri 36/VI Rantau Panjang. Data were collected through classroom observations, interviews with the teacher, and affective assessment instruments based on established affective indicators. The data were analyzed descriptively to illustrate how affective aspects were applied in mathematics teaching and learning. The findings indicate that the implementation of affective aspects in mathematics learning was carried out through several instructional strategies, such as assigning group tasks, providing praise for positive student responses, and encouraging student self-reflection on their learning processes. However, challenges remain in consistently applying specific affective indicators, particularly in maintaining student motivation when confronting complex mathematical topics. In conclusion, the implementation of affective aspects in mathematics learning at SD Negeri 36/VI Rantau Panjang contributes to creating a more positive learning environment, but systematic strengthening of affective indicators is needed for further improvement.